Q:

What is the value of c in the equation 2(x-3)+9=3(x+1)+x

Accepted Solution

A:
Answer:x = 0 Β (I must assume you had a typo since c is not a variable in this equation!Step-by-step explanation:Solve for x: 2 (x - 3) + 9 = 3 (x + 1) + x 2 (x - 3) = 2 x - 6: 2 x - 6 + 9 = 3 (x + 1) + x Grouping like terms, 2 x - 6 + 9 = 2 x + (-6 + 9): 2 x + (-6 + 9) = 3 (x + 1) + x 9 - 6 = 3: 2 x + 3 = 3 (x + 1) + x 3 (x + 1) = 3 x + 3: 2 x + 3 = 3 x + 3 + x Grouping like terms, 3 x + x + 3 = (3 x + x) + 3: 2 x + 3 = (3 x + x) + 3 3 x + x = 4 x: 2 x + 3 = 4 x + 3 Subtract 4 x from both sides: (2 x - 4 x) + 3 = (4 x - 4 x) + 3 2 x - 4 x = -2 x: -2 x + 3 = (4 x - 4 x) + 3 4 x - 4 x = 0: 3 - 2 x = 3 Subtract 3 from both sides: (3 - 3) - 2 x = 3 - 3 3 - 3 = 0: -2 x = 3 - 3 3 - 3 = 0: -2 x = 0 Divide both sides of -2 x = 0 by -2: (-2 x)/(-2) = 0/(-2) (-2)/(-2) = 1: x = 0/(-2) 0/(-2) = 0: Answer: Β x = 0